Temperature distribution and heat flow in cylindrical fin with heat source - Mohamad Azman, Poniran (2012)
Fin is used to increase heat transfer from heated surface to air. Industrial experience has shown that for same surface area, the fin array can transfer considerably more energy than single fin. Analysis of single fin is well known. However, when fins are placed in an arrangement, the convective patterns become consistent and the resulting heat transfer coefficient has not been predicted. The purpose of this project is to study the effectiveness of staggered cylindrical fin array with and without additional fin. Experimental data from the study is used to obtain the resulting heat transfer coefficient. The experimental study has been carried out through experiment by natural convection using test bench. The additional fin made from aluminum and fabricated in plate shape first before attach with staggered cylindrical array. From the measurement and experiment result, it shows the value of heat transfer coefficient for cylindrical array with additional fin is higher more than fifty percent compare to without additional fin. The relation of Nusselt number with heat transfer has been shown through the experimental result. The experimental result indicates that a staggered cylindrical fin array with additional fin performs better in heat transfer than staggered cylindrical fin array without additional fin. It showed that the additional fin affect the heat transfer much.